Students during the first six weeks of the 1933-34 Spring quarter. - Unknown:::Creator::::::::::::
Written on verso: "1st 6 weeks Spring Quarter 1933-1934; Dorothy Givens Greene, Ethlyn Rogers, Mary Buckman, Viona Ramelli."